The effect of Organizational Structure and Capital on the Saving Performance and Loan Units KPN Mertha Husada Gianyar, Bali, Indonesia - Tingkes, I Nyoman; Sirna, I Ketut; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2020)
the purpose of this study was to analyze the effect of strategy, structure, organizational culture, management style, systems and procedures, human resource management, and skills on the performance of the Mertha Husada Cooperative Savings and Loan Unit. The research was designed using quantitative methods and validated by qualitative methods. The study used 32 samples for quantitative research and 8 key informants for qualitative research. Quantitative data were analyzed using multiple linear correlations and regression techniques, while qualitative data were analyzed using reduce, display, and conclusion (drawing/verifying) techniques. The results of the study found (beta coefficient: 0.525) that the reform of the organizational structure by prioritizing the principle of balance of rights and obligations, authority, and management responsibility, as well as capital structuring using bank loan funds was the dominant factor in improving performance. The study also found that organizational culture factors were -0.22 and human resource management -0.006 had a negative effect on improving performance. From the research results it can be concluded that in an effort to improve the performance of the Mertha Husada Civil Servant Cooperative Savings and Loan Unit, in addition to improving the strategy, organizational structure and capital, management style, it is no less important to pay more attention to improving organizational culture and management. human Resources.